Randomized control study of ilio-inguinal nerve preservation versus neurectomy in lichtenstein tension free mesh repair of inguinal hernia - Mulkipatil, S. Y.; Kuntoji, S. B. (International Surgery Journal, 2016)
Background:Chronic post herniorrhaphy groin pain is defined as pain lasting > 3 months after surgery. Incidence of long term (= 1 year) post-operative neuralgia reported for Lichtenstein repair of inguinal hernia range from 6 - 29% Objective: To evaluate the effect of routine ilioinguinal nerve excision compared to nerve preservation on chronic groin pain and other sensory symptoms when performing lichtenstein inguinal hernia repair. Methods: 100 patients, diagnosed as inguinal hernia and candidate for nonemergency open mesh inguinal hernioplastic repair were enrolled and divided into 2 groups. All patients underwent Lichtenstein tension free mesh repair. Post-operative follow-up was done on day 1, 3, 7, at 1 month, 3 months and 6 months. Results:The incidence of post-operative severe pain was 36% versus 6% at POD-1, moderate pain 94% versus 22% at POD-3, moderate pain 78% versus 10% at POD-7 and no pain 8% versus 35% after 1 month of surgery respectively in the two groups. The incidence of post-operative hyperesthesia at groin in ilioinguinal nerve preservation group was 10%, 14%, 6% and 0% at POD-1, POD- 3, POD-7 and after 1 month respectively. Hyperesthesia was not observed in neurectomy group. Incidence of post-operative hypoesthesia and numbness at groin between the two groups at all post-operative follow up was found to be non-significant. Conclusions:- The study revealed decreased incidence of chronic groin pain after surgery in neurectomy group. The procedure is not significantly associated with additional morbidities like hyperesthesia, hyposthesia and numbness.